The drunken botanist : the plants that create the world's great drinks - Stewart, Amy (Algonquin Books of Chapel Hill, 2013)
Amy Stewart explores the dizzying array of herbs, flowers, trees, fruits, and fungi that humans have, through ingenuity, inspiration, and sheer desperation, contrived to transform into alcohol over the centuries.